2019
DOI: 10.1111/ijfs.14138
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of myosin regulatory light chain affects actomyosin dissociation and myosin degradation

Abstract: Summary This research aimed to investigate the influence of myosin regulatory light chain (MRLC) phosphorylation on actomyosin dissociation and myosin degradation in post‐mortem ovine longissimus thoracis (LT) muscle with a purpose for strategies to improve meat quality in practice. Data obtained show that the highest actomyosin dissociation occurred at 48 h post‐mortem. Based on the cluster analysis of the actomyosin dissociation degree at 48 h post‐mortem, samples were divided into high, middle and low‐actom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…MYLPF is a phosphoprotein with levels of phosphorylation modulated by the concerted action of Ca2+/calmodulin-dependent skeletal muscle myosin light chain kinase and protein phosphatase type 1 activities (Stull, Kamm, & Vandenboom, 2011). A number of studies in bovine, ovine and porcine have shown that changes in MYLPF phosphorylation levels are related to phenomena with impact in meat tenderness such as the skeletal muscle contraction force of fast-twitch fibers type IIb, the progress of rigor mortis, the response to pre-slaughter stress, actomyosin dissociation and myosin degradation (Muroya, Ohnishi-Kameyama, Oe, Nakajima, Shibata, & Chikuni, 2007;Franco et al, 2015;Chen et al, 2016;Lana & Zolla, 2016;Cao, Hou, Shen, Zhang, & Wang, 2019;Mato et al, 2019). In addition, we found that MYLPF is the single protein interacting with all partners (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…MYLPF is a phosphoprotein with levels of phosphorylation modulated by the concerted action of Ca2+/calmodulin-dependent skeletal muscle myosin light chain kinase and protein phosphatase type 1 activities (Stull, Kamm, & Vandenboom, 2011). A number of studies in bovine, ovine and porcine have shown that changes in MYLPF phosphorylation levels are related to phenomena with impact in meat tenderness such as the skeletal muscle contraction force of fast-twitch fibers type IIb, the progress of rigor mortis, the response to pre-slaughter stress, actomyosin dissociation and myosin degradation (Muroya, Ohnishi-Kameyama, Oe, Nakajima, Shibata, & Chikuni, 2007;Franco et al, 2015;Chen et al, 2016;Lana & Zolla, 2016;Cao, Hou, Shen, Zhang, & Wang, 2019;Mato et al, 2019). In addition, we found that MYLPF is the single protein interacting with all partners (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Gao, Li, Li, Du, and Zhang (2017) established an in vitro model through adding alkaline phosphatase and phosphatase inhibitor and reported that phosphorylation of myosin regulatory light chain in lamb positively regulated actomyosin dissociation during incubation at 4 °C, which benefited meat tenderness. Cao, Hou, Shen, Zhang, and Wang (2019) divided lamb samples into three groups of different actomyosin dissociation degrees according to the content of liberated actin in postslaughter sheep muscle and the results demonstrated that the phosphorylation of myosin regulatory light chain in lamb negatively regulated actomyosin dissociation. It is possible that other specific but not nonspecific phosphatase or protein kinase exist in postmortem muscle that phosphorylate certain sites of myosin regulatory light chain.…”
Section: Protein Phosphorylationmentioning
confidence: 99%